SISTEM INFORMASI GEOGRAFIS BERBASIS ANDROID SEBAGAI MEDIA INFORMASI PARIWISATA DI KABUPATEN BANYUMAS - Kusuma Ardhana, Yosef Murya; Utami, Emma; Luthfi, Emha Taufiq (Universitas Respati Yogyakarta, 2013)
Android was a smartphone which become an important part in human’s life that functioned as a means of communication. Nowadays, it was not only used as a means of comminication but also used to see the location or tourism geography. Tourism spots in Banyumas regency had diversity and uniqueness which were supported by facilities and transportation provided in the tourism spots. They could make the tourists visit those tourism spots easily. The local government had used mass media and also pamflet to inform and introduce tourism spots in Bayumas regency. However, those methods didn’t work for they could not inform the tourim spots widely to the tourists. By facing those problem, the writer made a geography information system which could give information about the tourism spots to the tourist s which used android that could be access easily. This system was integrated with database and could function well by implementing model ISO 9126. ISO 9126. This model gave validation from functionality, reliability, usability and efficiency so that it could maximize geography information system based on android which was made and developed. Keyword: Geographic Information System, ISO 9126, Functionality, Reliability, Usability, Efficiency Tourism, Android.